UJlKETAHANAN 104 GENOTIP KEDELAI (Glycine m.ax L) TERHADAP Ophiomyia phaseoli (Tryon) - -, Basuki (MAPETA, 2008)
The aim of the research is gctting vgenotipe of soybean resistance to Ophiomyia phaseoli (Tryon). Resistance test was done at Research Garden of Agriculture Faculty Padjadjaran University, Arjasari-Bandung  in February-April 2003. Research was designed using Randomized Block Design with 2 blocks replication. The treatment is 104 genotipe of soybean, observation was directed to resistance plant on Ophimyia phaseoli (Tryon). Rate of resistance was arranged by Resistance Category according to Ruswandi et all (1993). Results of the research shown that 104 genotipe was tested, there is no resistance genotipe (R), Genotipe number 24 occupy at the first resistance and including in Rather Sensitive (RS), 2 genotipes include Sensitive Category (S) and 101 genotipes Very Sensitive (VS) Key words : Resistance, Genotipe, Ophimyia phaseoli (Tryon)